Effect of the Implementation of Interdisciplinary Discharge Planning on Treatment Adherence and Readmission in Patients Undergoing Coronary Artery Angioplasty - Rahpeima, Elaheh; Bijani, Mostafa; Karimi, Shahnaz; Alkame, Abdulhakim; Dehghan, Azizallah (Investigación y Educación en Enfermería, 2023)
Objective. To determine the effect of interdisciplinary discharge planning on treatment adherence and readmission in the patients undergoing coronary artery angioplasty in the south of Iran in 2020. Methods. This experimental study had an intervention group and a control group with pre-test and post-test. 70 patients participated in the study who were randomly divided into the groups (intervention group (n=35) and control group (n=35)). In the intervention group, discharge planning was performed based on an interdisciplinary approach. Treatment adherence before, immediately, and one month after the intervention was evaluated with a 10-question survey scored from 1 to 5 (maximum score = 50), as well as readmission three months after the discharge was examined in both groups. Results. Before the intervention, there was no statistically significant difference between the intervention and the control groups in the treatment adherence score (18.22 versus 17.37; p=0.84) but immediately and one month after the intervention statistically significant differences between the groups were showed (21.51 versus 46.14 and 23.28 versus 43.12, respectively; p<0.001). Within three months after discharge, the readmission rate was 11.4% in the control group, while no readmission was reported in the intervention group. Within three months after discharge, the readmission rate was 11.4% in the control group, while no readmission was reported in the intervention group. Conclusion. The implementation of interdisciplinary discharge planning had positive effects on treatment adherence and readmission rate in patients undergoing coronary artery angioplasty; therefore, it is suggested that health care system managers make the necessary plans to institutionalize this new educational approach for other patients discharge planning.